César Vallejo y Gerardo Diego: una amistad poética humanísima - José Luis Bernal Salgado (Anuario de Estudios Filológicos, 2023)
In this paper, the personal and aesthetic relations between both poets are addressed, paying special attention to the role, and meaning of Vallejo’s work in the generation of '27 and the importance of Huidobro’s creationism and his environment in his poetry. For this purpose, the theoretical texts of Gerardo Diego on Vallejo and the letters between Diego, Vallejo and Larrea are analyzed. Furthermore, attention is also given to the meaning, in the plenitude of the generation of '27, of the Madrid edition of Trilce in 1930, Vallejo’s emblematic book, in which Gerardo Diego played a key role.